ANALISA TINGKAT KERACUNAN LOGAM BERAT Pb PADA TUKANG BECAK DAN PEDAGANG ASONGAN DI JALAN KAPTEN MUSLIM MEDAN - Eka Margaretha Sinaga; Erdina Gultom; Nova Florentina Ambarwati (LPPM Universitas Abdurrab, 2021)
Lead (Pb) is one of dangerous heavy metals that is toxic for human bodies. Lead can be found in the air in the form of air pollution which is produced by the fuel of motor vehicles. According to WHO, in 1995, the level of lead inside the human body can be divided into three levels which are, low (<10ppm), moderate (10-20 ppm), otherwise high (>20ppm) according to the category of pollution. A pedicab driver and a street vendor who frequent the street will surely very often be exposed to vehicle fumes which contains lead (Pb). This experiment is aimed to find out the level of Pb in the hair of pedicab drivers and street vendors around Kapten Muslim Street, Medan. From the overall population is randomly taken each 4 (four) hair samples from pedicab drivers and street vendors, and then continued with an examination using AAS (Atomic Absorption Spectrophotometer). From the result of the experiment, overall obtained that 1 (one) out of the rest is within the high level of toxicity (20,138 ppm), and then 2 (two) within the moderate level of toxicity (10,697 - 16,69 ppm), and 5 (five) others within the low level of toxicity (0,862â‰ˆ4,533 ppm). This shows that almost all pedicab drivers and street vendors around the Kapten Muslim Street, Medan are already poisoned with heavy metal, Pb, inside their bodies.